Mechanical milling and membrane separation for increased ethanol production during simultaneous saccharification and co-fermentation of rice straw by xylose-fermenting Saccharomyces cerevisiae. (June 2015) - Sasaki, Kengo; Tsuge, Yota; Sasaki, Daisuke; Teramura, Hiroshi; Inokuma, Kentaro; Hasunuma, Tomohisa; Ogino, Chiaki; Kondo, Akihiko
Highlights: Simultaneous saccharification and co-fermentation was conducted from rice straw. Mechanical milling increased enzymatic hydrolysis. Nanofiltration and ultrafiltration was applied on liquid fraction. Membrane separation increased ethanol production in co-fermentation. 52.0 g L −1 of ethanol was produced from whole rice straw. Abstract: Mechanical milling and membrane separation were applied to simultaneous saccharification and co-fermentation from hydrothermally pretreated rice straw. Mechanical milling with minimized 4 cycles enabled 37.5 ± 3.4 g L −1 and 45.3 ± 4.4 g L −1 of ethanol production after 48 h by xylose-fermenting Saccharomyces cerevisiae from solid fractions (200 and 250 g L −1 ) of pretreated rice straw with 5 filter paper unit g-biomass −1 cellulase (respectively, 77.3 ± 7.1% and 74.7 ± 7.3% of theoretical ethanol yield). Use of a membrane-based process including nanofiltration and ultrafiltration increased the sugar concentrations in the liquid fraction of pretreated rice straw and addition of this liquid fraction to 250 g L −1 solid fraction increased ethanol production to 52.0 ± 0.4 g L −1 (73.8 ± 0.6% of theoretical ethanol yield). Mechanical milling was effective in increasing enzymatic hydrolysis of the solid fraction and membrane separation steps increased the ethanol titer during co-fermentation, leading to a proposal for combining these processes for ethanol production from whole rice straw.